Meta-analysis The Validity of Learning Media E-learning Based on Edmodo for Senior High School Biology Learning - Annissa Delfira (Jurnal Biologi dan Pembelajarannya (JB&P), 2021)
The impact of Covid-19 affects aspects of life, one of which is the education aspect. The government makes policies in the education sector by shifting the face-to-face learning process online. Online learning can be done with e-learning media. The type of e-learning that can be used in the learning process is edmodo. Edmodo is a web, iOS and Android-based learning platform that looks like Facebook and is easy to use for beginners. Edmodo-based e-learning media can be used in the online learning process after meeting the eligibility indicators of validity. The validity results can be obtained based on an assessment of the aspects contained in the validity indicator according to the 2008 Ministry of National Education criteria, namely the aspects of feasibility of content, language, presentation and, graphics. Various study findings regarding validity indicators in previous studies are difficult to accumulate in quantitative form. Researchers used meta-analysis methods to obtain validity results that were easily accumulated and systematic, so researchers used 8 relevant articles. Based on the analysis of the 8 articles, the results show that 4 articles have fulfilled the validity criteria according to the Ministry of National Education (2008), namely the aspects of the feasibility of content, language, presentation, and graphics. Meanwhile, 4 other articles have not used the validity criteria according to the 2008 Ministry of National Education This shows that the 8 articles analyzed, only 4 articles met the valid qualifications according to the 2008 Ministry of National Education criteria.